2020
DOI: 10.3390/molecules25184060
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Extraction Conditions for Gracilaria gracilis Extracts and Their Antioxidative Stability as Part of Microfiber Food Coating Additives

Abstract: Incorporation of antioxidant agents in edible films and packages often relies in the usage of essential oils and other concentrated hydrophobic liquids, with reliable increases in antimicrobial and antioxidant activities of the overall composite, but with less desirable synthetic sources and extraction methods. Hydroethanolic extracts of commercially-available red macroalgae Gracilaria gracilis were evaluated for their antioxidant potential and phenolic content, as part of the selection of algal biomass for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This result suggests G. gracilis may harbor heat-sensitive compounds that are extracted more effectively at colder temperatures [8]. Although TPC-specific data on G. gracilis is limited, Reboleira et al [6] highlighted that by comparing aqueous and ethanolic extracts with similar antioxidant potential, a better yield was obtained using water. This study underscores G. gracilis as a promising source of versatile bioactive compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggests G. gracilis may harbor heat-sensitive compounds that are extracted more effectively at colder temperatures [8]. Although TPC-specific data on G. gracilis is limited, Reboleira et al [6] highlighted that by comparing aqueous and ethanolic extracts with similar antioxidant potential, a better yield was obtained using water. This study underscores G. gracilis as a promising source of versatile bioactive compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Gracilaria species, known for their significance in agar production, have gained attention as a promising source of bioactive compounds with potential applications in the food, feed, and pharmaceutical sectors [6]. Studies have revealed that Gracilaria gracilis, in particular, exhibits noteworthy antioxidant properties and radical scavenging activity.…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant potential of G. edulis is similar to that of tropical plants (Mustafa et al 2010). Further optimizing extraction conditions may produce different antioxidant activities (Reboleira et al 2020).…”
Section: Epiphytic Gracilaria Bioactive Potentialmentioning
confidence: 96%
“…Indonesia contributes significantly to the global seaweed production, particularly the commercial carrageenan producing seaweeds from the generas Kappaphycus and Eucheuma. West Nusa Tenggara (NTB) regency is among the top seaweed producers, along with East Nusa Tenggara, South Sulawesi, and Central Sulawesi (Rimmer et al 2021). However, currently the Indonesian seaweed industry is also facing various challenges and problems, which have caused a steady decline in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, and according to present results, previous in vitro studies have shown antioxidant properties of water extracts obtained from red macroalgae. Research has concerned red algae species such as Hypnea flagelliformis [38], Gracilaria verrucosa [39], and Gracilaria gracilis [40]. In all cases, the preservative behaviour was explained on the basis of the presence of phenolic compounds, flavonoids, carbohydrates, and alkaloids, which have the ability to neutralise free radicals.…”
Section: Antioxidant Activity Of Red Alga Extractsmentioning
confidence: 99%